Pengaruh K3 pada Perilaku Pekerja Konstruksi Di Pembangunan Gedung UM Buton - La Sianto; Muhammad Chaiddir Hajia (Jurnal Simki Economic, 2022)
The work on occupational health and safety management in the Buton UM building construction project and the lecture building is still lacking; Workplace safety and security services remain woefully inadequate and staff still lack health and safety care. The location of the study in this research is the construction of the New UM Buton Building, Baubau City, Southeast Sulawesi Province. In research on the Effect of Occupational Health and Safety on Worker Behavior, it will be held on September 21, 2021 – October 10, 2021. Data collection using the questionnaire method is usually done by distributing questionnaires to a number of predetermined respondents. From the results of the study, it is known that there are several main variables that affect the behavior of workers in the construction project of the UM Buton Building, occupational health and safety management with a mean value of 797.11, occupational health and safety regulations and procedures with a mean value of 217.25, communication with a mean value of 216. .75, worker competence with a mean value of 229.75, worker involvement with a mean value of 224,667, work environment with a mean value of 223.10 and worker behavior with a mean value of 175.00